The performance review knowledge of classical university students’ in the issues of academic and scientific integrity - Polotska, O. O. (Problems of Engineer-Pedagogical Education, 2018)
One of the basic aspects in educating highly-qualified and socially responsible university graduates nowadays is the principles of academic and scientific integrity for all parts to educational process. Notwithstanding the considerable effort that in the recent years been made by community as a whole and educationalists in particular, in practice we have still numerous cases of violating the above stated principles. The research contains a hypothetic assumption about one of possible reasons of violating ethical norms within university community, just about insufficient and fragmentary awareness of students of academic and scientific integrity issues. The method of anonymous questioning was used for test,. The exposure of insufficient understanding process of conditions creating for a sustainable system of academic and scientific integrity, structure and meaning of such a system, its participants were became as are search finding .